Pengaruh Aplikasi Kompos ampas Tebu Terhadap Pertumbuhan Dan Produktivitas Edamame (Glycine max (L) Merill) - Sinaga, Walmillleniari Elpat Ware The Gold; Suparto, Hairu; Jumar, Jumar (Universitas Lambung Mangkurat, 2024)
Bagasse is the rest of the sugarcane mill in the form of soft fiber flakes. In South Kalimantan, especially Banjarbaru city there are several sugarcane ice traders where a day on average produces sugarcane waste as much as 8-20 kg. This waste is usually not used anymore, so it can cause environmental disturbances. As a solution, bagasse can be used as compost. Edamame is a plant native to Japan, where the demand for edamame continues to increase. To increase the production of a plant, especially edamame, efforts are needed to add nutrients to the land through fertilization. The results of this study are expected to add information about the response of edamame to sugarcane pulp compost applications. The implementation of this research began in August 2021-November 2021 held at the Experimental Land of the Faculty of Agriculture, Lambung Mangkurat University. The method used in this study is a one-factor RandomIzed Group Design (RAK), with treatment D1 (control), D2 (bagasse compost 5 tons.ha-1), D3 (bagasse compost 10 tons.ha-1), D4 (bagasse compost 15 tons.ha-1), and D5 (bagasse compost 20.tons.ha-1), There are 5 groups. The results showed that bagasse compost only affects the height of edamame plants aged 3 MST and 4 MST, it does not affect other parameters. It is known that the compost dose of bagasse is 5 tons.ha-1 gives high results among other treatments.